Cytotoxic activities of the dichloromethane extracts from Andrographis paniculata (Burm. f.) nees - Tan, Maria Carmen S. (Animo Repository, 2018)
Introduction: Although diterpenes from Andrographis paniculata Burm.f. Nees have been found to have chemotherapeutic activity, a thorough investigation on the cytotoxic and anti-proliferative analyses on different cancer cell lines using these isolated constituents has not been achieved. Objectives: The primary objective of this study was to probe the cytotoxic capacity of the labdane diterpenoids andrographolide (1), 14-deoxyandrographolide (2), 14-deoxy-12-hydroxyandrographolide (3), and neoandrographolide (4) on mutant and wild type immortalized cell lines. Methods: Breast adenocarcinoma (MCF-7), colon carcinomas (HCT-116 and HT-29), small cell lung carcinoma (H69PR), human acute monocytic leukemia (THP-1), and wild type primary normal human dermal fibroblasts - neonatal cells (HDFn) were incubated with 1-4 and the degree of cytotoxicity was analyzed by employing the in vitro PrestoBlue® cell viability assay. Working solutions of 1-4 were prepared in complete cell culture medium to a final non-toxic DMSO concentration of 0.2%. The plates were incubated at 37°C with 5% CO2 in a 98% humidified incubator throughout the assay. Nonlinear regression and statistical analyses were done to extrapolate the half maximal inhibitory concentration, IC50. One-way ANOVA (P < 0.05) and multiple comparison, Tukey's post hoc test (P < 0.05), was used to compare different pairs of data sets. Results were considered significant at P < 0.05. Results: The highest cytotoxicity index was exhibited by the H69PR and 1 trials which displayed the lowest IC50 value of 3.66 μg/mL, followed by HT-29 treated with 2, HCT-116 and 1 trials, and H69PR treated with 4 (IC50 = 3.81, 3.82 and 4.19 μg/mL, respectively). Only 1 and 4 were detrimental towards MCF-7; while 1, 3, and 4 were degenerative against H69PR. Tukey's post hoc multiple comparison indicated no significant difference in the cytotoxicity of 1-4 on HCT-116 cells which afforded IC50 values ranging from 3.82 to 5.12 μg/mL. Evaluation of the two colon carcinoma cell lines showed that HCT-116 was categorically more susceptible to cellular damage caused by treatments with 1-4 than was HT-29. Cytotoxicity was not detected in THP-1 and HDFn cells (IC50 >100 μg/mL). Conclusion: Diterpenoids 1-4 isolated from the dichloromethane extract of the leaves of A. paniculata exhibited different cytotoxic activities against MCF-7, HCT-116, HT-29, H69PR. All constituents had comparable action on HCT-116 cells but were not found to be cytotoxic to normal HDFn cells and mutant THP-1 cells. © 2018 Journal of Natural Science, Biology and Medicine | Published by Wolters Kluwer - Medknow.